Analysis of the {4-Nicotinamido-4-Oxo-2-Butenoic Acid's} Electrochemical Polymerization as an Anti-Corrosion Layer on Stainless-Steel Alloys - Al-Timimi, Zahra; J Tammemi, Zeina (Journal of Sustainable Materials Processing and Management, 2022)
The [4-Nicotinamido-4-Oxo-2-Butenoic Acid] monomer was electropolymerized on 316-grade stainless steel to produce [poly4-Nicotinamido-4-Oxo-2-Butenoic Acid]. The structure and properties of the generated polymer layer were evaluated using SEM, cyclic voltammetry, and other techniques. The corrosion resistance of stainless steel, both uncoated and coated in a corrosive medium of 0.2M HCl solution was examined using an electrochemical polarisation technique at temperatures ranging from (293-323) K. Nanomaterials such as nano zinc oxide and graphene were introduced to monomer solutions at various concentrations to increase the corrosion resistance of stainless-steel surfaces. According to the findings, adding nano components to a polymeric coating increased its protective effectiveness. Thermodynamic and kinetic activation properties were also investigated. The percentage of protection efficiencies and polarisation resistance values of the covering polymer decreased as the temperature rose. As the temperature climbed, the corrosion current density increased, although the corrosion potential decreased. In SEM and AFM experiments, the development of a protective coating on the surface of 316-grade stainless steel was demonstrated to protect it.